2013
DOI: 10.1021/jm401465m
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Bioactivity of Cu2+ Bis-1,10-phenanthroline Artificial Metallonucleases with Sterically Functionalized Pendant Carboxylates

Abstract: The synthetic chemical nuclease, [Cu(1,10-phenanthroline)2](2+), has stimulated research within metallonuclease development and in the area of cytotoxic metallodrug design. Our analysis reveals, however, that this agent is "promiscuous" as it binds both dsDNA and protein biomolecules, without specificity, and induces general toxicity to a diversity of cell lineages. Here, we describe the synthesis and characterization of small-molecule metallonucleases containing the redox-active cation, [Cu(RCOO)(1,10-phen)2]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 58 publications
3
47
0
Order By: Relevance
“…The emission experiment has been widely used to further confirm the interaction between the test complexes and CT-DNA. One of the earlier studies in EB fluorescence displacement study, the K app value for [Cu(phen) 2 ](ClO 4 ) 2 was found to be 6.67 Â 10 5 M À1 [76]. Yang et al [68], K sv value of ternary copper(II) complex -[Cu-phen-tyr](H 2 O)](ClO 4 ) -was calculated to be 2.88 Â 10 3 M À1 (with gallic acid) and 0.61 Â 10 3 M À1 (without gallic acid).…”
Section: Fluorescence Spectroscopymentioning
confidence: 88%
See 1 more Smart Citation
“…The emission experiment has been widely used to further confirm the interaction between the test complexes and CT-DNA. One of the earlier studies in EB fluorescence displacement study, the K app value for [Cu(phen) 2 ](ClO 4 ) 2 was found to be 6.67 Â 10 5 M À1 [76]. Yang et al [68], K sv value of ternary copper(II) complex -[Cu-phen-tyr](H 2 O)](ClO 4 ) -was calculated to be 2.88 Â 10 3 M À1 (with gallic acid) and 0.61 Â 10 3 M À1 (without gallic acid).…”
Section: Fluorescence Spectroscopymentioning
confidence: 88%
“…Copper(II) complexes containing phen or substitute phen derivatives and L-amino acids have been described as potent cytotoxic agents, eliciting IC 50 [76]. In a similar previous report, Pivetta and coworkers have prepared binary copper(II) complexes -Cu(phen)(OH 2 ) 2 (ClO 4 ) 2 and [Cu(phen) 2 (OH 2 )](ClO 4 ) 2 -and studied cytotoxic activity four human cancer-derived cell lines: two from hematological cancers (CCRF-CEM acute T-lymphoblastic leukemia and CCRF-SB acute B-lymphoblastic leukemia) and two from carcinomas (K-MES-1 lung squamous carcinoma and DU-145 prostate carcinoma).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Interestingly, taking advantage of the effective association of phen with a variety of metals, it is possible to design systems with optimized DNA recognition properties. From a medicinal chemist perspective, this is an appealing feature for the development of metal complexes with potential antibacterial, anti-fungal, anti-inflammatory and anticancer activity [2].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] This radical chemistry, combined with the nucleic acid binding affinity of CuPhen, provide the reactive platform for DNA digestion through nucleoside H-atom abstraction. 14,15 In the context of DNA shuffling, CuPhen may also provide additional variation due to mutagenic base oxidation reactions (e.g. 8-oxo-deoxyguanosine; 8-oxo-dG), 16 however, it has not yet been established if digestion products from CuPhen are suitable for fragment annealing through primerless PCR (polymerase chain reaction) 17 ( Figure 1C).…”
mentioning
confidence: 99%
“…The mechanistic and stability aspects of the CuPhen complex have been reported extensively by this group. 15,16,18 Prior to DNA shuffling experiments, the selection and generation of a suitable α-PSA single chain variable fragment (scFv)-a bifunctional fusion protein having both antigen-binding capacity and biomarker activity applied for one-step immunodetection of biological agents 19 -was evaluated using the enzyme-linked immunosorbent assay (ELISA) against immobilised PSA using a pComb vector 20 (a small piece of DNA specifically designed for the construction of antibody libraries) scFv library stock previously generated at this institute (supplemental S4). From the selection of positive fluorescent signals against PSA (Table S3), plasmid DNA of a selected clone (from well F8, Figure S3) was prepared, sequenced by Eurofins Genomics GmbH ( Figure S1) and translated into protein sequence using ExPASy protein translation tool (Figure 2A pComb_F8).…”
mentioning
confidence: 99%